Investigation of the effect on the efficiency of phase change material placed in solar collector tank - Kilickap, Sinem; El, Emin; Yildiz, Cengiz (Elsevier, 2018)
In parallel with the increase in population, natural energy resources on earth started to run out. And this brought along tendency to new energy resources. Therefore, studies on new and renewable energy resources became intensified and especially researches about solar power as the most important renewable energy resource gained intensity. In this study, tank with latent heat storage in combination with hot water collector was designed and tests were held under Elazig climatic conditions. Thermal efficiencies obtained from collector system were compared to the efficiencies of a standard insulated tank. In accordance with this purpose the results of the tests, held on certain days in July-November, were commented. The highest thermal efficiency value in the study was obtained as 58% in July around hour 13:30 from the tank in which phase change material (PCM) was used.
Keywords: Solar power; Latent heat storage; Phase change material; Efficiency